Reshaping Chinese rural skilled workers flow in urban industrial clusters for clean air. (20th December 2022) - Liu, Na; Zhao, Shi; Shao, Quan; Li, Changan
Abstract: Sustainable development goals (SDGs) connect relationship between clean air action and creating decent work. In this study, a work matching model was proposed, coupled with cost loss of pollution emissions to quantify work inequity of rural skilled workers in 4 major pollution industries across 27 regions in China and mapped the spatial changes of labor flow. It was found that the employment scale in some traditional urban industrial clusters with high pollution emissions was shrinking, while that in some emerging ones with low pollution emissions was expanding. Considering the impact of clean air action on labor market, we also found that employment structure of rural skilled workers in the top 20% income regions was significantly better than that in the bottom 20%. We demonstrate that improving human capital of rural skilled workers not only increase individual income but also contribute to work equity under urbanization. Our approach can serve as an evaluation rule of thumb for labor market affected by environmental policy. Highlights: The mobile employment of rural skilled workers affected by urban air pollution controls are discussed. Responding to clean air policies reveals behavioral changes in individual work decisions. The spatial disparity of work matching is significant. Improving human capital of rural skilled workers can increase income and contribute to employment equality between urban and rural areas. Promoting clean air and ensuring decent work are a key issue in achieving sustainable development.